PENGARUH TRANSFORMATIONAL LEADERSHIP DAN ETHICAL CLIMATE TERHADAP WORK ENGAGEMENT DENGAN AFFECTIVE COMMITMENT SEBAGAI VARIABEL MEDIASI (PT DMS PROPERTINDO Tbk.) - Rizky Aulia (2023)
This research was conducted to determine the effect of transformational leadership and ethical climate on work engagement with affective commitment as a mediating variable (PT DMS Propretindo Tbk). The sample used in this study was 100 employees of PT DMS Propertindo Tbk. Data collection techniques using a questionnaire with a Likert scale. The data analysis technique used is descriptive data analysis, partial least squares (PLS), validity test, reliability test, hypothesis test and coefficient of determination test. This study uses the SmartPLS 3.0 program to analyze the data. The results of this study indicate that (1) transformational leadership has a significant effect on work engagement (2) ethical climate has a significant effect on work engagement, (3) affective commitment has a significant effect on work engagement, (4) transformational leadership has an effect on work engagement through affective commitment , (5) ethical climate affects work engagement through affective commitment.